(untitled) (Nexus International Journal of Science and Education, 2024)
This study examines the coping mechanisms of parents in navigating the challenges of multilanguage education for young learners in face-to-face learning settings. The research used a qualitative design and carefully considered ethical considerations in participant selection, data collection, analysis, and interpretation. The participants, parents selected through referrals, shared their experiences, challenges, and coping mechanisms related to supporting their children's academic development through multilanguage approaches. The study found that parents faced challenges in collaborating with teachers, supporting children with learning disabilities, and developing effective strategies. Coping mechanisms included building support networks, fostering positive relationships with learners, and providing sustained parental care. The study also highlighted the importance of parental involvement in school governance, seeking support from local partners, and advocating for policy reviews and actions. The findings suggest the need to translate the research into practical interventions at the district, school, and classroom levels. Continued collaboration among stakeholders is essential for improving educational practices, policies, and support systems for young learners and their families.